The political economy of streetspace reallocation projects: Aldgate Square and Bank Junction, London - Hickman, Robin; Huaylla Sallo, Katy (Journal of urban design, 2022)
Streetspace reallocation projects are often difficult to plan and implement, attracting great controversy with residents and other actors. This paper considers two streetspace reallocation projects, in Aldgate Square and Bank Junction, London. 15 in-depth interviews are used to explore the competing discourses on each project. The analysis covers the different viewpoints on perceived problems and opportunities, project impacts and effectiveness, distribution of benefits, technical assessment, participatory processes and the resulting sanctioned discourse. Using NVivo software, it examines the language used by the different actors in the process.